First Report of Botrytis cinerea on Golden Berry - Erper, I.; Çelik, Hüseyin; Türkkan, M.; Çebi Kiliçoǧlu, M. (Kluwer Academic Publishers, 2015)
Botrytis cinerea infection of golden berry was reported for the first time from Turkey. The pathogen caused grey mould disease. The disease was widely observed in a golden berry orchard in Samsun province (Eastern Black Sea region), Turkey. The fungus was identified as B. cinerea based on morphological characteristics and sequence analysis. © 2015, Australasian Plant Pathology Society Inc.
Keywords: Botrytis Cinerea; Golden Berry; Physalis Peruviana; Turkey